The Influence of Academic Supervision, School Culture, and Teacher Personality Competence on Teacher Work Discipline - Dianingsih, Dianingsih; Yuliejantiningsih, Yovitha; Supriyono, Supriyono (Journal of Innovation and Research in Primary Education, 2025)
Teacher work discipline is fundamental to educational quality, yet many elementary schools face significant challenges in maintaining adequate disciplinary standards. This study investigates the influence of academic supervision, school culture, and teacher personality competence on teacher work discipline in Bogorejo District, Blora Regency. A quantitative ex post facto design was employed with 113 elementary school teachers selected through proportional random sampling from a population of 158 teachers. Data were collected using validated questionnaires and analyzed using simple and multiple linear regression with SPSS version 22. Findings reveal that academic supervision significantly influences teacher work discipline (52.8%), school culture accounts for 44.3% of variance, and teacher personality competence demonstrates the strongest individual effect (59.4%). When combined, these three factors explain 63.5% of variance in teacher work discipline, with teacher personality competence emerging as the most dominant predictor. Results confirm theoretical frameworks linking supervision, organizational culture, and personality competence to professional behavior. The synergistic effect of these factors suggests that comprehensive approaches addressing individual characteristics and organizational contexts are essential for enhancing teacher discipline. Educational administrators should implement systematic supervision, cultivate positive school cultures, and strengthen teachers' personality competence through targeted professional development programs to achieve optimal disciplinary outcomes.